2008
DOI: 10.1172/jci33374
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between integrin αIIbβ3 and the serotonin transporter regulate serotonin transport and platelet aggregation in mice and humans

Abstract: The essential contribution of the antidepressant-sensitive serotonin (5-HT) transporter SERT (which is encoded by the SLC6A4 gene) to platelet 5-HT stores suggests an important role of this transporter in platelet function. Here, using SERT-deficient mice, we have established a role for constitutive SERT expression in efficient ADPand thrombin-triggered platelet aggregation. Additionally, using pharmacological blockers of SERT and the vesicular monoamine transporter (VMAT), we have identified a role for ongoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
134
2
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(152 citation statements)
references
References 50 publications
9
134
2
7
Order By: Relevance
“…NOS1 proteins have recently been found to associate with SERTs (Chanrion et al 2007), and we have shown that NOS activation is a critical step between A3 adenosine receptor activation and SERT stimulation; further focus on NOS1 structural and regulatory pathways seem worthy of investment for additional insights into autism risk. Finally, we recently documented the physical association and regulation of SERT by integrin b3 (Carneiro et al 2008). Integrin b3 has been associated with whole blood hyperserotonaemia (Weiss et al 2004) and with autism ( Weiss et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…NOS1 proteins have recently been found to associate with SERTs (Chanrion et al 2007), and we have shown that NOS activation is a critical step between A3 adenosine receptor activation and SERT stimulation; further focus on NOS1 structural and regulatory pathways seem worthy of investment for additional insights into autism risk. Finally, we recently documented the physical association and regulation of SERT by integrin b3 (Carneiro et al 2008). Integrin b3 has been associated with whole blood hyperserotonaemia (Weiss et al 2004) and with autism ( Weiss et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…14 Also the Leu33Pro ITGB3 SNP (rs5918) modulates SLC6A4 trafficking and transport activity. 19 Finally, several recently published studies have described significant SLC6A4 and ITGB3 interactions for both autism risk and 5-HT blood levels, with a male-specific effect. 10,[14][15][16][17]20 Despite these positive findings, several inconsistencies complicate their interpretation, possibly because of clinical and genetic heterogeneity in ASD.…”
Section: Introductionmentioning
confidence: 98%
“…En el 2008, Carneiro, et al, encontraron una evidencia funcional de la interacción entre las proteínas codificadas por los genes ITGB3 (αIIbβ3) y SLC6A4 (SERT) (89).…”
Section: Discussionunclassified
“…Estos resultados señalan que se requiere una adecuada expresión o señalización de αIIbβ3 para la función normal de la SERT (89). Las plaquetas que portan el polimorfismo Pro33 en ITGB3, cercano al polimorfismo evaluado en este trabajo, Leu59Pro, mostraron un incremento en la activación αIIbβ3, por la unión a fibrinógeno.…”
Section: Discussionunclassified
See 1 more Smart Citation